Reliability of the velocity achieved during the last repetition of sets to failure and its association with the velocity of the 1-repetition maximum - García-Ramos,Amador; Janicijevic,Danica; González-Hernández,Jorge M.; Keogh,Justin W.L.; Weakley,Jonathon (PeerJ, 2020)
Background This study aimed to determine the reliability of the velocity achieved during the last repetition of sets to failure (Vlast) and the association of Vlast with the velocity of the 1-repetition maximum (V1RM) during the paused and touch-and-go bench press (BP) exercises performed in a Smith machine. Methods A total of 96 healthy men participated in this study that consisted of two testing sessions. A single BP variant (paused BP or touch-and-go BP) was evaluated on each session in a randomized order. Each session consisted of an incremental loading test until reaching the 1RM, followed by two sets of repetitions to failure against a load ranging from 75% to 90% of 1RM. Results The reliability of Vlast was unacceptable for both BP variants (CV > 18.3%, ICC < 0.60). The correlations between V1RM and Vlast were small for the paused BP (r = 0.18) and moderate for the touch-and-go BP (r = 0.37). Conclusions Although these results suggest that Vlast could be a better indicator of the minimal velocity threshold than V1RM, the low reliability of Vlast and the similar values of Vlast for both BP variants suggest that a standard V1RM should be used to estimate the 1RM from the individualized load-velocity relationship.
Keywords: Bench press; Linear position transducer; Minimal velocity threshold; Strength testing; Velocity-based training